IoT-Based Data Analytics for the Healthcare Industry Techniques and Applications - Singh, S. K.; Singh, Ravi Shankar; Pandey, Anil Kumar; Udmale, Sandeep S; Chaudhary, Ankit (Academic Press, 2021)
IoT Based Data Analytics for the Healthcare Industry: Techniques and Applications explores recent advances in the analysis of healthcare industry data through IoT data analytics. The book covers the analysis of ubiquitous data generated by the healthcare industry, from a wide range of sources, including patients, doctors, hospitals, and health insurance companies. The book provides AI solutions and support for healthcare industry end-users who need to analyze and manipulate this vast amount of data. These solutions feature deep learning and a wide range of intelligent methods, including simulated annealing, tabu search, genetic algorithm, ant colony optimization, and particle swarm optimization. The book also explores challenges, opportunities, and future research directions, and discusses the data collection and pre-processing stages, challenges and issues in data collection, data handling, and data collection set-up. Healthcare industry data or streaming data generated by ubiquitous sensors cocooned into the IoT requires advanced analytics to transform data into information. With advances in computing power, communications, and techniques for data acquisition, the need for advanced data analytics is in high demand.
Online resource; title from digital title page (viewed on February 27, 2021)
Keywords: Medical statistics -- Data processing; Internet of things; Internet des objets; Medical statistics; Data processing